Penerapan Metode Drill dan Resitasi Sebagai Upaya Meningkatkan Hasil Belajar Matematika Materi Volume Kubus dan Balok pada Siswa Kelas V SDN I Terusan Makmur Tahun Pelajaran 2017/2018 - I Wayan Bawa (JURNAL PENDIDIKAN, 2020)
The problems that want to be examined in this research are: a) How do students improve their learning outcomes by applying the Drill and Recitation methods? b) How are the effects of the Drill and Recitation methods on student learning motivation? The objectives of this action research are: a) Want to know the improvement of student learning outcomes after the application of the Drill and Recitation methods, b) Want to know the effect of student motivation after the application of the Drill and Recitation methods. This research uses action research as many as three rounds. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is the fifth grade students. The data obtained are formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (65%), cycle II (75%), cycle III (95%). The conclusion of this research is the Drill and Recitation method can have a positive effect on the learning motivation of SDN I Terusan Makmur students, and this learning method can be used as an alternative to learning mathematics.